Approach and Policy Proposals to Address Climate Change - Jiménez, Roberto (2012)
This paper provides an assessment of mitigation policies for climate change (CC), from a critical perspective, based on some concepts of Ecological Economics and an analysis of certain approaches from Environmental Economics; Current policies have not been effective due to they start from premises that are not necessarily accurate or realistic; The use of market instruments, without parameters or standards of the physical world, besides not having goals and compliance obligations by countries, consumers and companies, causes a separation between the physical sustainability and results that markets in the area of trade from a financial perspective can achieve; There is a need to adopt policies that integrate obligations through standards, combined with market policies and other measures; Is relevant that developing countries can adapt, as these countries are the least prepared, those which have fewer benefits than of current model and those who receive the highest costs of the possible effects of CC.